The Bahay Biyaya Library of the Tahanang Walang Hagdanan a case study of the library in a rehabilitation agency - Perez, Marilou Grace B. (2006)
This study determined whether the Bahay Biyaya library and the libraries of the respective schools of the student-residents of Bahay Biyaya are fulfilling its objective in serving its disabled clientele. Systems Plus College Foundation in Cubao, University of Santo Tomas and Trinity College of Quezon City were covered in this study. In addition, the Tahanang Walang Hagdanan in Cainta Rizal was also included in order to provide a concrete description of the information needs of the disabled persons. In the study, it was found that: (1) only Systems Plus College Foundation Library has excellent library services for physically disabled persons ; (2) the Bahay Biyaya library has poor library services for persons with disabilities. Its library needs further improvement;(3) most of the respondents were employees/workers, aged 26 to 46 years old;(4) there were only 10 (40) students surveyed from Bahay Biyaya and only one (2.32) was surveyed from Tahanang Walang Hagdanan ; (5) a total of 13 (52) orthopedically disabled respondents with paraplegia, skeletal and muscular dystropies were from Bahay Biyaya while, there were 43 (100) orthopedically disabled respondents from Tahanang Walang Hagdanan and ; (6) The respondents were classified as/to be classified as the fully/ partially productive group of persons with disabilities.